THE METHOD OF MANAGEMENT WOMEN WITH ISTHMIC-CERVICAL INSUFFICIENCY - Мария Сергеевна Воронцова; Елена Николаевна Кравченко; Ольга Юрьевна Цыганкова (The Publishing House Medicine and Enlightenment, 2018)
Isthmic-cervical insufficiency (ICI) is one of the most common causes of spontaneous premature births. In II trimester of pregnancy in the structure of miscarriages, the share of ICI accounts for about 40 % of cases. The purpose - evaluate the effectiveness of the complex method of correction of isthmic-cervical insufficiency. Materials and methods. A simple, open, prospective, randomized study was performed on the basis of the City Clinical Perinatal Center in Omsk. Under observation, there were 60 patients aged 18-40 years in gestation period of 13-33 weeks 6 days with a proven diagnosis of «isthmic-cervical insufficiency». The main group included 30 patients who received treatment with a new combined method: the obstetric pessary «CVK», which differs from the analogues by a more anatomical ellipsoidal form and an increased number of perforations to improve the outflow of vaginal secretions in combination with intravaginal injection of micronized progesterone in a dosage of 100 mg 2 times a day and a drug normalizing the biocenosis of the vagina, as a lyophilized culture of lactobacilli L. casei rhamnosus Doderleini in a dosage of 340 mg, 1 capsule intravaginally at night 2 times a week. The comparison group consisted of 30 patients who received treatment: obstetric silicone pessary + micronized progesterone at a dosage of 200 mg per day intravaginally. The outcomes of pregnancy and childbirth were evaluated. Results. The total number of premature births in the main group was 4 (13.3 %) compared to 12 (40 %) in the comparison group (p = 0,023). Based on the results of the study, a statistically significant reduction in patients with recurrent vaginal flora (p = 0,0001) was obtained and, due to a decrease in this indicator, a general decrease in the number of women with complications of pregnancy was registered (p = 0,019). The conclusion. The proposed method of correction of isthmic-cervical insufficiency is more effective than existing methods and can be recommended for wide application.